Participation, engagement and collaboration in newsmaking : a postfoundational perspective - Declercq, Jana; Jacobs, Geert; Macgilchrist, Felicitas; Vandendaele, Astrid (Discourse approaches to politics, society, and culture, 2021)
"This book brings together new research on the practices of newsmaking. Participation, engagement and collaboration have long been heralded as a vision, goal or emerging practice in the news. The claim in this volume is that they have now become sedimented as the common-sense baseline for everyday newsmaking routines. The issue for newsmakers is not 'whether' to engage with readers and users, but 'how' to engage with them. The contributions span a wide range of newsmaking contexts, including analytics-based online headline testing, the communication efforts of a Brussels-based free marketeer thinktank, collaborative science journalism and rapidly changing journalistic sourcing and writing routines from legacy to social media. Together they argue for a postfoundational perspective, which observes how participation, engagement and collaboration have emerged as a 'foundation' which is no longer questioned, but which can lead to new tensions in newsmaking. As such, the book provides inspirational reading for anyone in the social sciences and humanities who is interested in understanding how the ubiquity of participation, engagement and collaboration in the making of the news impacts on issues of power, transparency and control in the twenty-first century"--